2015
DOI: 10.1109/tia.2015.2405499
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical Loss Components and Heat Transfer in an Axial-Flux PM Machine

Abstract: This paper investigates components of mechanical loss together with heat transfer effects in an axial-flux PM motor. The mechanical loss components generated within electrical machines are well known, however, their prediction or derivation has not been widely reported in the literature. These, together with the electromagnetic loss sources and heat transfer effects are crucial and must be accounted for when considering high-power-density, high-speed and/or compact machine designs. This research is focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 30 publications
(47 reference statements)
2
24
0
1
Order By: Relevance
“…More importantly, the results were verified with the numerical simulations by Wrobel et al [21] as well as the experimental data by Howey et al [24]. This verification can give us trust in the CFD modeling used in this study.…”
Section: Robustness Of the Correlationssupporting
confidence: 82%
See 1 more Smart Citation
“…More importantly, the results were verified with the numerical simulations by Wrobel et al [21] as well as the experimental data by Howey et al [24]. This verification can give us trust in the CFD modeling used in this study.…”
Section: Robustness Of the Correlationssupporting
confidence: 82%
“…He showed that an increase in the magnet groove depth from 2 to 18 mm can noticeably raise the windage losses (up to 60 W) through the generator with the rotor diameter of 220 mm, gap size distance of 2 mm and the angular velocity of 1500 rpm. Wrobel et al [21] also performed CFD simulations to assess the windage losses in an AFPMSM. They investigated the aerodynamic effects occurring within the air-gap.…”
Section: Introductionmentioning
confidence: 99%
“…It can be mentioned that in some studies on self-ventilated electric motors, in the absence of air flow measurements, it was assumed that the flow velocity of air in the channels was equal to 75% of the peripheral speed of the fan rotor [12]. The results of the heat exchange on electric motor confirmed that the heat is mainly transferred by conduction from the stator/winding assembly to the housing [13].…”
Section: Methodsmentioning
confidence: 88%
“…The reasons for the difference between the simulated and the tested efficiency maps of the ferrite magnet prototype has been explored, and they are 1) The simplified windage and friction loss model used in the dynamic model cannot expect to be accurate, especially when the motor is operating with an efficiency more than 90 %. The windage loss characterisation of the PMBLDC motor requires a detailed study using nonmagnetic dummy rotors and computational fluid dynamic models [23], [24]. The lack of mechanical loss characterisation prevents the extraction of electromagnetic losses other than the conduction loss from the test data.…”
Section: Discussionmentioning
confidence: 99%